(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
According to the World Health Organization (WHO), more than 700,000 people die each year due to antibiotic-resistant infections. It is estimated that by 2050, this figure could reach 10 million. This poses a massive threat to the global community, not only medically but also socio-economically. Antibiotic resistance negatively impacts the reliability of healthcare systems, the duration of disease treatment, and overall healthcare costs.